The mechanisms of skeletal muscle atrophy in response to transient knockdown of the vitamin D receptor in vivo. (24th December 2020) - Bass, Joseph J.; Kazi, Abid A.; Deane, Colleen S.; Nakhuda, Asif; Ashcroft, Stephen P.; Brook, Matthew S.; Wilkinson, Daniel J.; Phillips, Bethan E.; Philp, Andrew; Tarum, Janelle; Kadi, Fawzi; Andersen, Ditte; et al.
Abstract : Key points: Reduced vitamin D receptor (VDR) expression prompts skeletal muscle atrophy. Atrophy occurs through catabolic processes, namely the induction of autophagy, while anabolism remains unchanged. In response to VDR‐knockdown mitochondrial function and related gene‐set expression is impaired. In vitro VDR knockdown induces myogenic dysregulation occurring through impaired differentiation. These results highlight the autonomous role the VDR has within skeletal muscle mass regulation. Abstract: Vitamin D deficiency is estimated to affect ∼40% of the world's population and has been associated with impaired muscle maintenance. Vitamin D exerts its actions through the vitamin D receptor (VDR), the expression of which was recently confirmed in skeletal muscle, and its down‐regulation is linked to reduced muscle mass and functional decline. To identify potential mechanisms underlying muscle atrophy, we studied the impact of VDR knockdown (KD) on mature skeletal muscle in vivo, and myogenic regulation in vitro in C2C12 cells. Male Wistar rats underwent in vivo electrotransfer (IVE) to knock down the VDR in hind‐limb tibialis anterior (TA) muscle for 10 days. Comprehensive metabolic and physiological analysis was undertaken to define the influence loss of the VDR on muscle fibre composition, protein synthesis, anabolic and catabolic signalling, mitochondrial phenotype and gene expression. Finally, in vitro lentiviral transfection was used to induce sustained VDR‐KD in C2C12 cells to analyse myogenic regulation. Muscle VDR‐KD elicited atrophy through a reduction in total protein content, resulting in lower myofibre area. Activation of autophagic processes was observed, with no effect upon muscle protein synthesis or anabolic signalling. Furthermore, RNA‐sequencing analysis identified systematic down‐regulation of multiple mitochondrial respiration‐related protein and genesets. Finally, in vitro VDR‐knockdown impaired myogenesis (cell cycling, differentiation and myotube formation). Together, these data indicate a fundamental regulatory role of the VDR in the regulation of myogenesis and muscle mass, whereby it acts to maintain muscle mitochondrial function and limit autophagy. Key points: Reduced vitamin D receptor (VDR) expression prompts skeletal muscle atrophy. Atrophy occurs through catabolic processes, namely the induction of autophagy, while anabolism remains unchanged. In response to VDR‐knockdown mitochondrial function and related gene‐set expression is impaired. In vitro VDR knockdown induces myogenic dysregulation occurring through impaired differentiation. These results highlight the autonomous role the VDR has within skeletal muscle mass regulation.